UJI KADAR ASAM LAKTAT PADA KEJU KACANG TANAH (Arachis hypogaea L.) BERDASARKAN VARIASI WAKTU DAN KONSENTRASI BAKTERI Lactobacillus bulgaricus DAN Streptococcus lactis - Ulfa Mutia; Chairul Saleh; Daniel - (JURNAL KIMIA MULAWARMAN, 2013)
The research has done of “Test content of free fatty acids in cheese peanut (Arachis hypogaea L.) by variations storage period difference and the concentration of bacteria Streptococcus lactis and Lactobacillus bulgaricus.” The cheese processing includes: coagulation, formation or salting and storage period. And the addition of skim milk and starter bacteria Streptococcus lactis and Lactobacillus bulgaricus. In the research purpose for determination the effect of concentration of starter bacteria Streptococcus lactis and Lactobacillus bulgaricus and storage period difference to free fatty acid of peanut cheese. This research used 2 factors and conducted by three time repetition. The first factor was the concentration of starter (1%, 2% and 3%) and the second factor storage period (5, 10 and 15 days). The results showed that the highest free fatty acid of starter bacteria at a concentration of 3% and storage period of 10 and 15 days. The lowest free fatty acid of starter bacteria at a concentration of 1% and storage period at zero day.Keywords: Peanut, free fatty acid, fermentation, cheese.